Hierarchical genetic clusters for phenotypic analysis - Matta, Luiza Barbosa da; Tomé, Lívia Gracielle Oliveira; Salgado, Caio Césio; Cruz, Cosme Damião; Silva, Letícia de Faria (Acta Scientiarum. Agronomy, 2013)
Methods to obtain phenotypic information were evaluated to help breeders choosing the best methodology for analysis of genetic diversity in backcross populations. Phenotypes were simulated for 13 characteristics generated in 10 populations with 100 individuals each. Genotypic information was generated from 100 loci of which 20 were taken at random to determine the characteristics expressing two alleles. Dissimilarity measures were calculated, and genetic diversity was analyzed through hierarchical clustering and graphic projection of the distances. A backcross was performed from the two most divergent populations. A set of characteristics with variable heritability was taken into account. The environmental effect was simulated assuming x~N(0, σ2). For hierarchical clusters, the following methods were used: Gower Method, average linkage within the cluster, average linkage among clusters, the furthest neighbor method, the nearest neighbor method, Ward's method, and the median method. The environmental effect and heritability of the analyzed variables had an influence on the pattern of hierarchical clustering populations according to the backcrossed generations. The nearest neighbor method was the most efficient in reconstructing the system of backcrossing, and it presented the highest cophenetic correlation. The efficiency of the nearest neighbor method was the highest when the analysis involved characteristics of high heritability.

Visando auxiliar o melhorista na escolha da melhor metodologia para análises de diversidade genética em populações de retrocruzamento avaliaram-se os métodos baseados em informações fenotípicas. Os fenótipos foram simulados para 13 características, geradas em 10 populações com 100 indivíduos cada. Geraram-se informações genotípicas de 100 locos, dos quais 20 foram tomados ao acaso para determinar as características, manifestando dois alelos. Medidas de dissimilaridade foram calculadas, e analisou-se a diversidade genética por meio agrupamento hierárquico e projeção gráfica das distâncias. A partir das duas populações mais divergentes fez-se o retrocruzamento. Considerou-se um conjunto de características com herdabilidade variável. Simulou-se o efeito ambiental admitindo distribuição normal, com média zero e variância σ2. Para as análises de agrupamentos hierárquicos utilizaram-se os métodos: Método de Gower, Ligação média dentro de grupo, Ligação média entre grupo, Vizinho mais distante, Vizinho mais próximo, Método de Ward, Método da mediana. O efeito ambiental e a herdabilidade das variáveis analisadas influenciaram o padrão de agrupamento de populações sob retrocruzamento. Em características de herdabilidade elevada, o método do Vizinho mais próximo foi o mais eficiente em reconstituir o retrocruzamento, além de ter apresentado a maior correlação cofenética, sendo considerada a melhor metodologia a priori e a posteriori.
Keywords: Hierarchical clustering; Genetic diversity; Backcrossing